STRATEGI PENGEMBANGAN OBJEK WISATA NGARAI KOTO BARANGAI SEBAGAI DAYA TARIK DI DESA WISATA BUKITAPIT KOTA BUKITTINGGI - Rozi Yuliani; Dewi Anggraeni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Tourism Aspect is one of the important things for to increase country’s economic. One of the potential tourism object is Ngarai Koto Barangai, located in Kelurahan Bukit Apit Puhuh, Bukittinggi City. This research aim is to identify factors in the development of tourism object in desa wisata bukit apit puhun. Also to know the development strategy which needs to develop ngarai koto barangai to be a potential tourism object in desa wisata kelurahan bukit apit Bukittinggi City. The analysis tools used in this research is SWOT analysis .The formulation of development strategies in Ngarai Koto Barangai are important to be noted from the various aspects such as tourists, transportation means, tourism object, infrastructures and supporting facilities within the tourism object, as well as need to be supported with funds and qualified human resources. Suggestions in this research is important to increase society and government awareness to develop Ngarai Koto Barangai to be a tourism destination in kelurahan bukit apit puhun, which still lacking the cooperation with various related parties; the synergy between the Government with the academics in the provision of competent human resources in the field of tourism' also improvement the utilization of information technology to introduce and to promote potential tourism to the worldwide community.